Sulphate-resistent barium-containing portland cement for cementing oil and gas wells - Zolotarov, Kyrylo (Національний технічний університет "Харківський політехнічний інститут", 2025)
The recent decline in gas production in Ukraine is largely attributet not to the depletion of its resource base, but to the overexploitation of easily recoverable reserves and the lack of development of more complex ones.
Keywords: Ukraine; gas production; hydrocarbon reserves; HPT conditions; reservoir pressure; reservoir temperature; resource depletion